Detailed Clinical and Psychological Phenotype of the X-linked HNRNPH2-Related Neurodevelopmental Disorder. (February 2021) - Bain, Jennifer M.; Thornburg, Olivia; Pan, Cheryl; Rome-Martin, Donnielle; Boyle, Lia; Fan, Xiao; Devinsky, Orrin; Frye, Richard; Hamp, Silke; Keator, Cynthia G.; LaMarca, Nicole M.; Maddocks, Alexis B.R.; et al.
Abstract : Objective: To expand the clinical phenotype of the X-linked HNRNPH2 -related neurodevelopmental disorder in 33 individuals. Methods: Participants were diagnosed with pathogenic or likely pathogenic variants in HNRNPH2 using American College of Medical Genetics and Genomics/Association of Molecular Pathology criteria, largely identified via clinical exome sequencing. Genetic reports were reviewed. Clinical data were collected by retrospective chart review and caregiver report including standardized parent report measures. Results: We expand our clinical characterization of HNRNPH2 -related disorders to include 33 individuals, aged 2–38 years, both females and males, with 11 different de novo missense variants, most within the nuclear localization signal. The major features of the phenotype include developmental delay/intellectual disability, severe language impairment, motor problems, growth, and musculoskeletal disturbances. Minor features include dysmorphic features, epilepsy, neuropsychiatric diagnoses such as autism spectrum disorder, and cortical visual impairment. Although rare, we report early stroke and premature death with this condition. Conclusions: The spectrum of X-linked HNRNPH2 -related disorders continues to expand as the allelic spectrum and identification of affected males increases.